Research on the History of Church Universities in China over the Past 30 Years and Modern Chinese Education - NG Tze Ming, (Journal of Research for Christianity in China (JRCC), 2025)
Since 1985, when Professor Zhang Kaiyuan, President of Central China Normal University, accepted an unexpected challenge, he embarked on another journey in his life—dedicating himself to pioneering research on the history of Chinese church-affiliated universities. This endeavor has now spanned three decades. This October, the Center for the Study of Religion and Chinese Society at Shanghai University and the American journal Chinese Christian Studies jointly hosted an academic symposium titled “Christianity and Modern Chinese Education.” The author believes this presents an opportune moment to examine the developmental trajectory of research on the history of Chinese church universities over the past three decades, as well as its impact on and potential relationship with modern Chinese education. This paper will focus on three areas of inquiry: (1) Professor Zhang Kaiyuan's historical education; (2) Moral education at Nanjing Normal University; and (3) Religious studies and liberal arts education at Peking University.